Impact of moisture regimes on yield and soil microbial population in pea (Pisum sativum) - SINGHAL, NEHA; SIAG, MUKESH; SHARMA, POONAM; SHARDA, RAKESH; SINGH, HARPINDER (The Indian Journal of Agricultural Sciences, 2022)
Method of application of irrigation to the crop plays one of the most crucial roles in plant growth, development and overall production of the crop. To study the effect of different types of irrigation methods on the yield of the pea (Pisum sativum L. var. PB-89) crop, a field experiment was conducted at the research farm of the Punjab Agricultural University, in the winter of 2016–17 and 2017–18. Five treatments, viz. drip irrigation on crop grown on level field (T1), drip irrigation on crop grown on ridges (T2), flood irrigation (T3) and furrow irrigation (T4) all at 100% ET level and rainfed irrigation (T5) were compared. Each method of irrigation application had a unique soil moisture pattern during the crop growing period. Soil microbial properties were also studied for different treatments and although there was non-significant difference in microbial population among treatments, there was significant difference of biologicalactivity of the microbes with respect to different irrigation treatments, as reflected by the recorded dehydrogenase activity of the soil.  Population of microbes was maximum at flowering stage. Yield of the crop varied significantly with the method of irrigation used. Maximum yield was obtained under drip irrigation treatment